Hvad er en videnskabelig flersproget idiomordbog? - Farø, Ken; Hallsteinsdóttir, Erla (Nordiske Studier i Leksikografi, 2007)
We address the question of what might deserve the name ”a scientific multilingual idiom dictionary”. Few interlingual idiom dictionaries actually call themselves so or try to leave the impression that they are scientifically based. Why is that so? It may have to do with the very character of the object itself, idioms, and the special interest many people show in them. We want to demonstrate that there are no principal barriers against such a project: A catalogue of lexicological and lexicographical measures and methodologies already exist. What could be questioned, however, is the lexicographical relevance of the matter. On the other hand, there may still be pragmatic arguments in favour of such a dictionary. A metalexicographical discussion of this dilemma will be given.